A degree-day model for predicting adult emergence of the citrus gall wasp, Bruchophagus fellis (Hymenoptera: Eurytomidae), in southern Australia. (May 2021) - Mo, Jianhua; Stevens, Mark M.
Abstract: The citrus gall wasp, Bruchophagus fellis, is a serious pest of citrus in southeast Australia and the ability to accurately predict its highly synchronised adult emergence periods is critical for its effective management. We monitored emergence of the citrus gall wasp for six years during 2010–2017 in southern Australia, yielding a total of 22 site-by-year datasets from two citrus production regions and multiple citrus varieties. For each dataset, the proportions of emerged wasps on different monitoring dates were related to the corresponding degree-days using a 2-parameter Weibull function. The two degree-day parameters, the lower development threshold temperature and biofix date, were estimated at 8 °C and August 1 respectively by cross-validation of a series of candidate values using the sum of squared differences between the predicted and observed median emergence dates as the performance indicator. According to the final fitted Weibull function, 5, 50, and 95% emergence occur when 560, 723 and 835 degree-days above 8 °C have accumulated after August 1. The predicted median emergence dates differed from the corresponding observed median emergence dates by an average of 2.8 days across the 22 datasets. The average deviations for 5 and 95% emergence were slightly larger, at five and four days, respectively. Observed degree-days for median emergence did not differ significantly between the two citrus production regions, indicating there is no need for separate degree-day models for different regions. Based on the degree-day model, an interactive, online timing tool has been developed, allowing growers to use local weather station data to predict when the gall wasp is likely to emerge in average, warm, and cool years. Highlights: A degree-day model was developed for the emergence of the citrus gall wasp. 50% emergence occurs when 723 DD above 8 °C have accumulated after August 1. Average prediction accuracy is ±2.8 days across 22 datasets. An online tool was published to help citrus growers time their control operations.